2016
DOI: 10.4103/0971-5916.178615
|View full text |Cite
|
Sign up to set email alerts
|

Phage therapy of staphylococcal chronic osteomyelitis in experimental animal model

Abstract: Background & objectives:Methicillin resistant Staphylococcus aureus (MRSA) are the commonest cause of osteomyelitis. The aim of this study was to evaluate the role of an alternative therapy i.e. application of S. aureus specific bacteriophages in cases of osteomyelitis caused by MRSA in animal model.Methods:Twenty two rabbits were included in this study. The first two rabbits were used to test the safety of phage cocktail while the remaining 20 rabbits were divided into three groups; group A (n=4) to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(45 citation statements)
references
References 25 publications
2
43
0
Order By: Relevance
“…It can be concluded that the diagnosis of osteomyelitis is more often based on radiographic evidence of bone lysis, production and necrosis. Our results were in an agreement with Chandan et al (2016). There are numerous reports in the literature using animal models of osteomyelitis for investigating pathogenesis, diagnosis, and treatment of bone infections.…”
Section: Bone Radiographical Findingsupporting
confidence: 82%
“…It can be concluded that the diagnosis of osteomyelitis is more often based on radiographic evidence of bone lysis, production and necrosis. Our results were in an agreement with Chandan et al (2016). There are numerous reports in the literature using animal models of osteomyelitis for investigating pathogenesis, diagnosis, and treatment of bone infections.…”
Section: Bone Radiographical Findingsupporting
confidence: 82%
“…Radiographs of the femur were obtained on post-wounding days 7, 14 and 28 in order to evaluate alterations of osteomyelitis, such as periosteal reaction, sclerosis and osteolysis ( 10 ).…”
Section: Methodsmentioning
confidence: 99%
“…To overcome this problem, phage cocktails containing multiple strains of phages have been developed, and may be necessary for clinical efficacy. 40,43 There is also concern over the use of viruses within human hosts, without knowledge of their potential side effects. However, little if any side effects have been identified in numerous clinical reports of bacteriophage use, with no reports of anaphylaxis.…”
Section: Bacteriophagesmentioning
confidence: 99%